Integrated data mining, network pharmacology and molecular docking to explore the medication rules and mechanism of traditional Chinese medicine compound in the treatment of acne - Wanyun Zhu; Ziyan Cheng; Qimei Xie; Bin Sun; Min Wei; Songfeng Wang; Yiyun Qian; Pingping Song (In Silico Pharmacology, 2026)

Dietary supplementation of Radix Isatidis polysaccharides improves meat quality in broilers by regulating lipid metabolism, antioxidant defense, and the gut-muscle axis - Wei Wang; Wenbin Ouyang; Haibo Xiao; Panpan Shi; Pingping Li; Jianguo Zeng; Meirong Song; Sundus Javed; Peng Huang (Research in Veterinary Science, 2026)

Species-specific environmental niches govern biogeographic patterns and seasonal dynamics of the harmful algal genus Phaeocystis in Chinese seas - Pingping Shen; Jiayi Shi; Xuejun Fu; Qingshang Song; Yue Xue; Xiyan Wang; Mengqi Dong; Haiping Li (Environmental Pollution, 2026)

Feature fusion and improved DeepLab v3+ for simultaneous segmentation and statistics of surviving and withered Pinus sylvestris - Pingping Zhou; Bing Bai; Anzhou Zhao; Ziheng Song; Jian Zhang (International Journal of Remote Sensing, 2026)

A robust estimation method for canopy chlorophyll content based on FOD and hierarchical weighting combination models - Jie Zhang; Xiaoyu Song; Yuanyuan Ma; Laigang Wang; Liang Sun; Li Li; Heguang Sun; Chunkai Zheng; Pingping Li; Xia Jing; Guijun Yang; Chunjiang Zhao (European Journal of Agronomy, 2026)

18–26 years: A critical window for synergistic reduction of atmospheric pollutant and greenhouse gas emissions - Pingping Song; Zhenhui Gao; Zhiyuan Duan; Junhua Song; Haiyan Duan; Siyan Chen; Bailin He; Meng Gao (Environmental Impact Assessment Review, 2026)

Event- and annual-scale precipitation extremes enhance groundwater recharge at the ecological restoration catchment of hilly and gully region - Meina He; Yunqiang Wang; Yali Zhao; Li Wang; Ziliang Zhang; Yi Song; Pingping Zhang; Zimin Li (Ecological Engineering, 2026)

Linking runoff and sediment characteristics to karst development degree in small watershed - Zhengyi Tang; Rui Li; Li Qin; Tao Song; Benjin Yu; Pingping Yang; Jun Jing; Linlv Xiao (CATENA, 2026)

OSMAC-activated and GNPS-guided investigation of alkaloids from an endophytic fungus Aspergillus sp. FH-1 of Valeriana officinalis L. - Hao Fan; Pingping Wu; Xin Wang; Yuze Li; Chong Deng; Wei Wang; Xiaomei Song; Xin Zhang; Dongdong Zhang (Biochemical Systematics and Ecology, 2026)

A Fiber-Driven Finite Element Model for Predicting Residual Limb Soft Tissue Deformation: Applications in Prosthetic Socket Design - Ling Wang; Ziyan Qiu; Lei Tang; Fuhao Huang; Pingping Wei; Senay Mihcin; Changning Sun; Hongyuan Zhao; Lei Shi; Song Han; Dichen Li (Annals of Biomedical Engineering, 2026)

From hidden danger to rapid detection: silver-enhanced urchin-like tungsten oxide MEMS sensors for Listeria monocytogenes detection in refrigerated dairy - Xingyu Wang; Pingping Liu; Haijie Cai; Cheng Zhao; Weihao Wu; Haixia Zhou; Yayao Song; Zhaohuan Zhang; Yong Zhao; Yongheng Zhu (Food Chemistry, 2025)

Iontophoresis-Enhanced Transdermal Delivery of Hyaluronic Acid: Mechanisms, Molecular Weight Effects, and Application Potential - Qinghui Zhang; Dangwei Li; Jian Song; Xianmei Meng; Pingping Zhao; Yihua Zhou; Jun Qian (Journal of Pharmaceutical Innovation, 2025)

How does land use transfer affect ecosystem services in Northwest China? - Pingping Zhou; Yuansheng Tian; Jun Zhai; Xiaoyan Song; Yi Li; Wenyi Sun (Ecological Engineering, 2025)

Ox-LDL Induces Neuron Apoptosis and Worsens Neurological Outcomes in aSAH via Fas/FADD Pathway - Yabin Song; Chen Yu; Dandan Bo; Junqi Sun; Yong Wang; Pingping Chen; Hanming Wu; Linghong Hong; Zhennan Ye; Long Zhang; Diangui Zhou (Molecular Neurobiology, 2025)

A GNSS PPP integrity monitoring algorithm based on ARKF and MHSS - Ershen Wang; Tengli Yu; Xinhui Sun; Pingping Qu; Tingyu Chen; Xuebao Hong; Song Xu; Zexin Liu (Advances in Space Research, 2025)

Synergistic mechanism of magneto-optical sensing mediated by magnetic response protein Amb0994 and LOV-like protein Amb2291 in Magnetospirillum magneticum AMB-1 - Haitao Chen; Changyou Chen; Haoyu Zhao; Yuanyuan Wei; Pingping Wang; Long-Fei Wu; Tao Song (Journal of Photochemistry and Photobiology B: Biology, 2025)

Inversion of biophysical parameters of potato based on an active learning pool-based sampling strategy - Yuanyuan Ma; Xiaoyu Song; Jie Zhang; Di Pan; Haikuan Feng; Guijun Yang; Chunxia Qiu; Heguang Sun; Chunkai Zheng; Pingping Li (International Journal of Remote Sensing, 2025)

Microbiologically influenced corrosion inhibition of carbon steel by a novel bacterium, Photobacterium sp., in simulated marine environment - Tingting Zhu; Liling Xu; Lijing Yang; Pingping Zhao; Xinglong Zhu; Zhengli Wu; Zhenlun Song (Environmental Research, 2025)

Satellite navigation signal quality monitoring algorithm based on DBO-SVM - Ershen Wang; Yilin He; Tengli Yu; Liang Liu; Song Xu; Pingping Qu; Tao Pang (Advances in Space Research, 2024)

Strong seasonality and unsuspected diversity of haptophytes explored by metabarcoding analysis in the Chinese seas - Cunchao Wu; Yue Xue; Qingshang Song; Jiehui Yin; Yanying Zhang; Pingping Shen (Marine Environmental Research, 2024)

Metabolic Heterogeneity and Potential Immunotherapeutic Responses Revealed by Single-Cell Transcriptomics of Breast Cancer - Shicong Tang; Qing Wang; Ke Sun; Ying Song; Rui Liu; Xin Tan; Huimeng Li; Yafeng Lv; Fuying Yang; Jiawen Zhao; Sijia Li; Pingping Bi; et al. (Apoptosis, 2024)

The effect of Ca2+-calcineurin signaling pathway on the antifungal activity of Pd-D-V against Botrytis cinerea - Yao Yu; Xinru Li; Yiping Hou; Min Wei; Yiyun Qian; Yuxin Zhou; Min Yin; Yanqin Jiang; Pingping Song (Pesticide Biochemistry and Physiology, 2024)

Dynamics of solar-induced chlorophyll fluorescence (SIF) and its response to meteorological drought in the Yellow River Basin - Hao Wu; Pingping Zhou; Xiaoyan Song; Wenyi Sun; Yi Li; Songbai Song; Yongqiang Zhang (Journal of Environmental Management, 2024)

Heat transfer performance study of Cu-ethanol/ethylene glycol/propylene glycol-water nanofluids in a wavy-walled tube heat exchanger - Liang Zhang; Jiabai Song; Pingping Qu; Shuangzhu Wang; Huimin Zhang; Hairui Wang; Hongfa Liu; Taiyan Lu (Journal of Environmental Chemical Engineering, 2024)

Edible composite films: enhancing the postharvest preservation of blueberry - Dongfang Shi; Boya Zhao; Pingping Zhang; Ping Li; Xinpei Wei; Kai Song (Horticulture, Environment, and Biotechnology, 2024)

Sarafloxacin hydrochloride exposure disrupts gut microbiota and increases shrimp susceptibility to Vibrio anguillarum infection - Haonan Sha; Tingting Song; Pingping Zhan; Xinxu Zhang; Jiong Chen; Jinbo Xiong (Aquaculture, 2024)

Effect of liquid nitrogen spray quick-freezing technology on the quality of bamboo shoots, Dendrocalamus brandisii from Yunnan Province, China - Zhenmei Fan; Hui Shen; Tenggen Hu; Lijuan Yu; Yujuan Xu; Jijun Wu; Pingping Shi; Xianliang Song; Yuanshan Yu (Journal of Food Engineering, 2024)

Ultrafine Ru nanoparticles stabilized by V8C7/C for enhanced hydrogen evolution reaction at all pH - Yanju Long; Yong Shen; Pingping Jiang; Hui Su; Jiahui Xian; Yamei Sun; Jun Yang; Haili Song; Qinghua Liu; Guangqin Li (Science Bulletin, 2024)

Investigation on damage-permeability model of dual-porosity coal under thermal-mechanical coupling effect - Pingping Ye; Bobo Li; Chonghong Ren; Haosheng Song; Jiale Fu; Xuehai Wu (Gas Science and Engineering, 2024)

N-nitrosodimethylamine exposure to zebrafish embryos/larvae causes cardiac and spinal developmental toxicity - Xiaoyi Liu; Jinge Song; Xiaotao Yan; Pingping Li; Jinhua Zhang; Bin Wang; Jing Si; Yong Chen (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Intensive land restoration projects alter mechanisms underpinning spatiotemporal soil moisture variability at a catchment scale: A case study in China - Yali Zhao; Yunqiang Wang; Wei Hu; Hui Sun; Lijun Qi; Lan Xu; Yi Song; Pingping Zhang (Journal of Hydrology, 2024)

Investigating the long-term response of plateau vegetation productivity to extreme climate: insights from a case study in Qinghai Province, China - Hexuan An; Xiaoyan Song; Ziyin Wang; Xubo Geng; Pingping Zhou; Jun Zhai; Wenyi Sun (International Journal of Biometeorology, 2024)

Potato late blight severity monitoring based on the relief-mRmR algorithm with dual-drone cooperation - Heguang Sun; Xiaoyu Song; Wei Guo; Mei Guo; Yanzhi Mao; Guijun Yang; Haikuan Feng; Jie Zhang; Ziheng Feng; Jiao Wang; Yuanyuan Ma; Chunkai Zheng; et al. (Computers and Electronics in Agriculture, 2023)

Diversity and geographical distribution of haptophyte Phaeocystis in the Chinese seas based on metabarcoding analysis - Qingshang Song; Yue Xue; Yanying Zhang; Jiehui Yin; Pingping Shen (Journal of Oceanology and Limnology, 2023)

Incorporation of ascorbic acid and L-cysteine in sodium carboxymethyl cellulose coating delays color deterioration and extends the shelf-life of fresh-cut asparagus lettuce (Lactuca sativa var. angustata) - Renying Yu; Huibo Song; Yanan Chen; Nan Shi; Hui Shen; Pingping Shi; Huosheng Shu; Xiaoxue Kong; Lijuan Yu; Haibo Luo (Postharvest Biology and Technology, 2023)

Mediating and spatial spillover effects of public participation in environmental pollution governance mediated via traditional and new media - Pingping Ma; Yan Song; Ming Zhang (Journal of Environmental Management, 2023)

How does environmental tax affect enterprises’ total factor productivity? Evidence from the reform of environmental fee-to-tax in China - Longke Wang; Pingping Ma; Yan Song; Ming Zhang (Journal of Cleaner Production, 2023)

Structural and functional diversity of the microbiome during the Phaeocystis globosa winter bloom in the southern Yellow Sea of China - Yue Xue; Qingshang Song; Dongmei Li; Xiyan Wang; Hui Liu; Cunchao Wu; Pingping Shen (International Biodeterioration & Biodegradation, 2023)

Collagens for surimi gel fortification: Type-dependent effects and the difference between type I and type II - Yadong Zhao; Kunyu Lu; Xinyue Piao; Yan Song; Libin Wang; Rusen Zhou; Pingping Gao; Heng Yen Khong (Food Chemistry, 2023)

Evaluation of Cd2+ stress on Synechocystis sp. PCC6803 based on single-cell elemental accumulation and algal toxicological response - Yao Tao; Man He; Beibei Chen; Gang Ruan; Pingping Xu; Yixue Xia; Gaofei Song; Yonghong Bi; Bin Hu (Aquatic Toxicology, 2023)

Insights into carbon loss reduction during aerobic composting of organic solid waste: A meta-analysis and comprehensive literature review - Pingping Ye; Linfa Fang; Dan Song; Muyuan Zhang; Ronghua Li; Mukesh Kumar Awasthi; Zengqiang Zhang; Ran Xiao; Xinping Chen (Science of The Total Environment, 2023)

Investigation of toxic effect of mercury on Microcystis aeruginosa: Correlation between intracellular mercury content at single cells level and algae physiological responses - Wenxiao Tang; Man He; Beibei Chen; Gang Ruan; Yixue Xia; Pingping Xu; Gaofei Song; Yonghong Bi; Bin Hu (Science of The Total Environment, 2023)

Development and Application of Three-Dimensional Bioprinting Scaffold in the Repair of Spinal Cord Injury - Dezhi Lu; Yang Yang; Pingping Zhang; Zhenjiang Ma; Wentao Li; Yan Song; Haiyang Feng; Wenqiang Yu; Fuchao Ren; Tao Li; Hong Zeng; Jinwu Wang (Tissue Engineering and Regenerative Medicine, 2022)

DNA and histone modifications as potent diagnostic and therapeutic targets to advance non-small cell lung cancer management from the perspective of 3P medicine - Guodong Zhang; Zhengdan Wang; Pingping Song; Xianquan Zhan (EPMA Journal, 2022)

The genome of a mangrove plant, Avicennia marina, provides insights into adaptation to coastal intertidal habitats - Dongna Ma; Qiansu Ding; Zejun Guo; Chaoqun Xu; Pingping Liang; Zhizhu Zhao; Shiwei Song; Hai-Lei Zheng (Planta, 2022)

Complete genomic characterization of a reassortment isolate of Sophora yellow stunt virus from Sophora alopecuroides in China - Shuang Song; Pingping Sun; Mingxiu Ju; Xuan Zhang; Xingqi Yang; Lei Zhang; Zhengnan Li (Journal of Plant Pathology, 2022)

First Report on Large-Scale Phaeocystis globosa Bloom in the Southern Yellow Sea, China - Dongmei Li; Yue Xue; Qingshang Song; Fuxu Cui; Yujuan Ma; Mengmeng Tong; Pingping Shen (Frontiers in Marine Science, 2022)
From late November 2021, a large-scale Phaeocystis globosa bloom occurred for the first time in the southern Yellow Sea, covering an area of over 630 km 2 and lasting for nearly 40 days. Two investigations, combined with satellite remote sensing, were successively conducted on December 11 and 23, 2021 to study the bloom dynamics and impacts. During the bloom, the average temperature decreased from 11.8°C to 10.0°C and salinity increased slightly from 30.9 to 31.3. The pH remained consistently at 8.22, while dissolved oxygen and chlorophyll -a content decreased dramatically from 7.23 mg L -1 to 5.82 mg L -1 , 8.72 μg L -1 to 2.35 μg L -1 , respectively. The concentration of nitrate and silicate decreased moderately, whereas nitrite, ammonium and phosphate increased obviously, especially the ammonium content, elevated from 0.90 μmol L -1 to 1.39 μmol L -1 during two investigations. Meanwhile, the P. globosa colony densities varied between 10 colonies L -1 and 185 colonies L -1 , with a mean of 70.0 colonies L -1 on Dec. 11, and decreased dramatically to an average of 1.46 colonies L -1 on Dec. 23. Similarly, single cells decreased from 3.6×10 6 cells L -1 to 1.05×10 6 cells L -1 accordingly. Moreover, diameter of the colonies varied from 0.5 cm to 2.0 cm, with an average diameter of 1.0 cm, and no colonies smaller than 0.5 cm was observed in the bloom. Correlation analysis indicated temperature and salinity related with the colony abundance positively (P<0.001) and negatively (P<0.05), respectively, and silicate and nitrite concentration showed significant positive effects on solitary cell density (P<0.05). No mortality of marine organisms was observed and the haemolytic activity of Phaeocystis samples was low, varying between 13.07 Hu L -1 and 19.22 Hu L -1 . Based on phylogenetic analysis, this P. globosa strain may represent a possible different ecotype which prefers low temperature and is less or nontoxicity.

Addition of humic acid accelerates the growth of Euglena pisciformis AEW501 and the accumulation of lipids - Panpan Fan; Pingping Xu; Yuxuan Zhu; Xiaojie Tu; Gaofei Song; Yanxia Zuo; Yonghong Bi (Journal of Applied Phycology, 2022)

Biocompatibility of marine magnetotactic ovoid strain MO-1 for in vivo application - Changyou Chen; Pingping Wang; Long-Fei Wu; Tao Song (Journal of Oceanology and Limnology, 2021)

Dietary exposure to fatty acid esters of monochloropropanediols and glycidol of 2- to 3-year-old children attending nursery schools from two areas in China using the duplicate-diet collection method - Liang Jiang; Zhou Jing; Wang Yibaina; Song Yan; Xu Lili; Zhong Yanxu; Yong Ling; Zhou Pingping; Sui Haixia; Zhang Lei (Food Additives & Contaminants: Part A, 2021)

Spatio-temporal Variation of Water Heat Flux Using MODIS Land Surface Temperature Product over Hulun Lake, China During 2001–2018 - Boyu Zhao; Jia Du; Kaishan Song; Pierre-André Jacinthe; Xiaoyun Xiang; Haohao Zhou; Zhichao Yang; Liyan Zhang; Pingping Guo (Chinese Geographical Science, 2020)

Mechano growth factor pretreatment yield mechanical stimuli induced cell stress responses in ligament fibroblasts of osteoarthritis via activating ATF-2 - Yu Ma; Yang Song; Linhao Li; Lili Dong; Chunli Wang; Pingping Wang; Li Yang (Biotechnology Letters, 2020)

An effective method for identification of three mussel species and their hybrids based on SNPs - Xingqiang Chen; Ronghua Li; Chunlin Wang; Changkao Mu; Weiwei Song; Lei Liu; Ce Shi; Pingping Zhan (Conservation Genetics Resources, 2020)

Molecular identification reveals hybrids of Mytilus coruscus × Mytilus galloprovincialis in mussel hatcheries of China - Weijia Zhang; Ronghua Li; Xingqiang Chen; Chunlin Wang; Zhongqi Gu; Changkao Mu; Weiwei Song; Pingping Zhan; Ji Huang (Aquaculture International, 2020)

Is phosphorus a limiting factor to regulate the growth of phytoplankton in Daya Bay, northern South China Sea: a mesocosm experiment - Xingyu Song; Meiting Tan; Ge Xu; Xinying Su; Jihua Liu; Gaungyan Ni; Yao Li; Yehui Tan; Liangmin Huang; Pingping Shen; Gang Li (Ecotoxicology, 2019)

Light irradiation helps magnetotactic bacteria eliminate intracellular reactive oxygen species - Kefeng Li; Pingping Wang; Chuanfang Chen; Changyou Chen; Lulu Li; Tao Song (Environmental Microbiology, 2017)
Summary Magnetotactic bacteria (MTB) demonstrate photoresponse. However, little is known about the biological significance of this behaviour. Magnetosomes exhibit peroxidase‐like activity and can scavenge reactive oxygen species (ROS). Magnetosomes extracted from the Magnetospirillum magneticum strain AMB‐1 show enhanced peroxidase‐like activity under illumination. The present study investigated the effects of light irradiation on nonmagnetic (without magnetosomes) and magnetic (with magnetosomes) AMB‐1 cells. Results showed that light irradiation did not affect the growth of nonmagnetic and magnetic cells but significantly increased magnetosome synthesis and reduced intracellular ROS level in magnetic cells. Quantitative reverse transcription polymerase chain reaction (qRT‐PCR) was performed to analyse the expression level of magnetosome formation‐associated genes ( mamA , mms6 , mms13 and mmsF ) and stress‐related genes ( recA , oxyR , SOD , amb0664 and amb2684 ). Results showed that light irradiation upregulated the expression of mms6 , mms13 and mmsF . Furthermore, light irradiation upregulated the expression of stress‐related genes in nonmagnetic cells but downregulated them in magnetic cells. Additionally, magnetic cells exhibited stronger phototactic behaviour than nonmagnetic ones. These results suggested that light irradiation could heighten the ability of MTB to eliminate intracellular ROS and help them adapt to lighted environments. This phenomenon may be related to the enhanced peroxidase‐like activity of magnetosomes under light irradiation.

Resveratrol Pretreatment Decreases Ischemic Injury and Improves Neurological Function Via Sonic Hedgehog Signaling After Stroke in Rats - Pingping Yu; Li Wang; Fanren Tang; Li Zeng; Luling Zhou; Xiaosong Song; Wei Jia; Jixiang Chen; Qin Yang (Molecular Neurobiology, 2017)

Variations in silicate concentration affecting photosynthetic carbon fixation by spring phytoplankton assemblages in surface water of the Strait of Malacca - Gang Li; Qiang Lin; Pingping Shen; Guangyan Ni; Xingyu Song; Shengfu Wang; Yanzhi Fan; Liangmin Huang; Yehui Tan (Acta Oceanologica Sinica, 2013)

Latitudinal variability (6°S–20°N) of early summer phytoplankton species compositions and size-fractioned productivity from Java Sea to South China Sea - Gang Li; Liangmin Huang; Huaxue Liu; Zhixin Ke; Qiang Lin; Guangyan Ni; Jianqiang Yin; Kaizhi Li; Xingyu Song; Pingping Shen; Yehui Tan (Marine Biology Research, 2012)